Explorations of the Semantic Learning Machine Neuroevolution Algorithm - Gonçalves, Ivo (2020)
Gonçalves, I., Seca, M., & Castelli, M. (2020). Explorations of the Semantic Learning Machine Neuroevolution Algorithm: Dynamic Training Data Use, Ensemble Construction Methods, and Deep Learning Perspectives. In W. Banzhaf, E. Goodman, L. Sheneman, L. Trujillo, & B. Worzel (Eds.), Genetic Programming Theory and Practice XVII: Genetic and Evolutionary Computation (pp. 39-62). [Chapter 3] (Genetic Programming Theory and Practice XVII). Springer. https://doi.org/10.1007/978-3-030-39958-0_3